Early and late outcomes following valve sparing aortic root reconstruction: The ANZSCTS database - Dhurandhar, V.; Parikh, R.; Vallely, M.; Wilson, M.; Black, D.; Tran, L.; Reid, Christopher; Bannon, P. (Elsevier Australia, 2015)
Introduction: Valve sparing aortic root reconstruction has become an alternative to traditional aortic root replacement with a valved conduit. There have been various modifications but the two broad types are aortic root reimplantation and the aortic root remodelling procedure. We present the early and late outcomes following valve sparing aortic root reconstruction surgery in Australia and New Zealand.Methods: We reviewed the ANZSCTS database for patients undergoing these procedures. Preoperative, intraoperative and postoperative variables were analysed. Multivariable regression was performed to determine independent predictors of 30-day mortality. We also obtained 5- and 10-year survival estimates by cross-linking the ANZSCTS database with the National registry of Births, Deaths and Marriages.Results: Between January 2001 and January 2012, 169 consecutive patients underwent valve sparing aortic root reconstruction procedures. The mean age of the study population was 54.4 years with 31.4% being females. Overall, 9 patients (5.9%) died within 30 days post procedure and 5 patients (3%) had permanent strokes. However, out of 132 elective cases, only 5 patients died (3.8%). Independent predictors of 30 day mortality were female gender (odds ratio [OR] 5.65, p=0.025), preoperative atrial arrhythmia (OR 6.07, p=0.035) and acute type A aortic dissection (OR 7.71, p=0.01). Long term survival was estimated as 85.3% and 72.7% at 5- and 10-years, respectively.Discussion: Along with an acceptable rate of early mortality and stroke, valve sparing aortic root reconstruction procedures have good long term survival according to the ANZSCTS database. As promising procedures for pathologies that impair the aortic root integrity, they can be adopted more widely, especially in Australian and New Zealand centres with experienced aortic units. Future studies are planned to assess freedom from valve deterioration and repeat surgery.